AN ITEM ANALYSIS ON ENGLISH PROFICIENCY TEST OF NECESA 2.0 AT UNIVERSITAS PGRI WIRANEGARA - Jannah, Hawa Innafiil; Mabaroh, Barotun; Istiqomah, Dewi Masitho (Universitas Bunda Mulia, 2025)
English is used widely as the international language. The mastery of English skills has a standardization. One way to analyze (either a person qualified or not) is using a test. Competition can be used as the language testing for English learners. From this background, the researcher intended to analyze the quality of the written test form by NECESA 2.0 which is held by English Student Association. The researcher wanted to analyze the content validity, reliability, item distractor, item difficulty, and discriminating power on English Proficiency Test item of NECESA 2.0.The researcher used mixed method in this research. This study aims to collect data by calculating the results of the five characteristics of a good test. The research subjects were the participants of English Proficiency Contest of NECESA 2.0. There are 63 senior high school students. This research used two instruments, there are documentation and human instrument.Based on the findings, English Proficiency Contest of NECESA 2.0 already has very good content validity. The content that has stated in each item is 94% suitable with the English ATP (syllabus). The coefficient value of the reliability of the tests is 0,935. This test also has good item difficulty value. The test-maker is successful make a good proportion in levelling the difficulty of EPC of NECESA 2.0 test. The results of the discriminating power analysis of the participants' answers to the EPC questions can be seen that most of the differentiating power (52%) or 52 items on the EPC are sufficient or in satisfactory category. The item distractor of English Proficiency Contest of NECESA 2.0 still has many unfunctional distractor. There are 148 distractors categorized as poor ID and 76 distractors categorized as very poor ID. It can conclude that distractors has poor distractor and it really needs to be revised.